Characterization of trichomonad species and strains by PCR fingerprinting - Vanácová, S; Tachezy, J; Kulda, J; Flegr, J (The Journal of eukaryotic microbiology, 1997)
The random amplified polymorphic DNA (RAPD) technique was used for phylogenetic analysis of trichomonads, for intraspecies genealogical study of Trichomonas vaginalis strains, and for assessment of intrastrain polymorphism in Trichomonas vaginalis. The phylogenetic tree for 12 trichomonad species showed certain discrepancies with current models of trichomonad evolution. However, it shows that RAPD traits retain phylogenetically relevant information. The results of intraspecies analyses of 18 Trichomonas vaginalis strains suggested some concordance between the genetic relationship of strains and their geographic origin. They also suggested a concordance between the strain genetic relationships and the resistance to metronidazole. A concordance was also found with respect to the severity of disease observed in donor patients but not with the results of laboratory virulence assays. No concordance was found between genetic relationship of strains and strain infection with a dsRNA Trichomonas vaginalis virus (TVV). The latter suggests that TVV might be transmitted horizontally among Trichomonas vaginalis populations. The identity of RAPD patterns of clones isolated from in vitro cultures and those of the cultures reisolated independently from the same patient within a period of six weeks suggests that individual Trichomonas vaginalis strains are not polymorphic and that the RAPD patterns are stable. Therefore, the RAPD technique seems useful for addressing various clinically relevant issues.
Keywords: Random Amplified Polymorphic DNA Technique; protozoální DNA; Drug Resistance; technika náhodné amplifikace polymorfní DNA; Trichomonadida; polymorfismus genetický; fylogeneze; virulence; Phylogeny; DNA fingerprinting; DNA Fingerprinting; Metronidazole; Virulence; léková rezistence; DNA, Protozoan; Antitrichomonal Agents; Polymorphism, Genetic; Trichomonas vaginalis; Animals; lidé; metronidazol; Humans; zvířata; antitrichomonádové látky